2011
DOI: 10.1016/j.phrs.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil concentrate delays sensitivity to thermal nociception in mice

Abstract: Fish oil has been used to alleviate pain associated with inflammatory conditions such as rheumatoid arthritis. The anti-inflammatory property of fish oil is attributed to the n-3 fatty acids docosahexaenoic acid and eicosapentaenoic acid. Contrarily, vegetable oils such as safflower oil are rich in n-6 fatty acids which are considered to be mediators of inflammation. This study investigates the effect of n-3 and n-6 fatty acids rich oils as dietary supplements on the thermally induced pain sensitivity in healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…For the treatment of various painful conditions in clinical placebo-controlled studies, the consumption of FO supplementation of human is equivalent to EPA/DHA 45-100 mg/kg body weight per day [10,11,24]. According to the previous studies [25,26], we chose 4% FO supplementation to investigate the effect on the PDN and its mechanisms. The present study demonstrated that FO could attenuate both mechanical allodynia and thermal hyperalgesia of diabetic rats, which is probably a sum of its anti-inflammatory and modulating insulin signaling actions.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of various painful conditions in clinical placebo-controlled studies, the consumption of FO supplementation of human is equivalent to EPA/DHA 45-100 mg/kg body weight per day [10,11,24]. According to the previous studies [25,26], we chose 4% FO supplementation to investigate the effect on the PDN and its mechanisms. The present study demonstrated that FO could attenuate both mechanical allodynia and thermal hyperalgesia of diabetic rats, which is probably a sum of its anti-inflammatory and modulating insulin signaling actions.…”
Section: Discussionmentioning
confidence: 99%
“…Failure to provide bedding material for a rat to make a nest for her pups can lead to hyperalgesia in those pups when they become adults 55,56 , and the handling of young animals (for example, related to injections, and involving the stress of maternal separation) can cause long-term alterations in pain sensitivity 41,[57][58][59][60][61][62][63] . A growing literature also documents the effect of diet on pain sensitivity [64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80] . In one case, differences in the soy content of rat chow turned out to be wholly responsible for a failure to replicate in Baltimore the findings of studies originally performed in Jerusalem 65 .…”
Section: Jeffrey S Mogilmentioning
confidence: 99%
“…ASICs are excitatory cation channels directly gated by extracellular protons of many painful conditions [117,118]. However, recent studies have demonstrated that omega-3 PUFAs decrease the mRNA expression of ASIC1a, ASIC3 and TRPV1, suggesting a reduced inflammatory status, which may be the reason for the increased pain threshold [102].…”
Section: Omega-3 Fatty Acids Combined With Morphinementioning
confidence: 99%